Secret reserve prices by uninformed sellers - Pasha Andreyanov; El Hadi Caoui (Quantitative Economics, 2022)
If bidders are better informed than the seller about a common component of auction heterogeneity, the seller can allocate more efficiently by keeping her reserve price secret and revising it using submitted bids. We build a model of a first-price auction under unobserved auction heterogeneity-imperfectly observed by the seller-that captures this rationale and derive conditions for identification. An application to French timber auctions, where such revisions are widely used, shows that having perfect information about unobserved auction heterogeneity would increase surplus by 5.22%. Combining a secret reserve price with learning from submitted bids reduces this surplus gap by up to 84%.
Keywords: C57; D44; Q23; 330; First-price auction; reserve price; unobserved heterogeneity; timber industry